Verification of an empirical model on Religiosity, Direct Action and Satisfaction with Life: differences between students from public and private universities (Research, Society and Development, 2020)
Currently, the university environment is considered as a context that can favor the emergence of problems related to mental health and quality of life of students who are subjected to pressure through deadlines and results, also dealing with the various uncertainties arising from the social and economic. In this sense, it was intended to understand about three variables that can contribute with the student to the experience of university life: Religiosity, Direct Action and Satisfaction with Life. Differences in indicators between public and private sector students were investigated. The study was quantitative with data collection using psychometric instruments validated with 583 university students aged 18 to 63 years. As for the type of university, 246 are students from public universities and 337 are students from private universities. Descriptive analyzes (mean and standard deviation), analysis of Person's linear correlation and Student's t test were performed to compare means between independent samples. The results showed that the variables considered showed a significant positive correlation and that there was a significant difference in the indicators of students from public and private universities. It is considered that the research objective was achieved by contributing with empirical evidence relevant to this area of study.